The Silent Threat: Understanding and Managing Diabetic Retinopathy - Borowiec, Kinga; Borowiec, Agnieszka; Kwaśniewska, Paulina; Biernikiewicz, Julia; Wilewska, Anna; Biernikiewicz, Milena; Pomirski, Bartosz; Pomirska, Agata; Alabrudziński, Konstanty; Kałachurska, Miszela (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Diabetic retinopathy (DR) is a common complication of diabetes mellitus, characterized by damage to the blood vessels in the retina. It is one of the leading causes of blindness in adults worldwide. This article aims to explore the pathophysiology, risk factors, basic rules of patient screening, DR classification and current treatment approaches for DR, with the goal of improving awareness and understanding of this vision threatening condition. Materials and methods: A review was conducted in PubMed and Google Scholar including publications regarding diabetic retinopathy and its’ pathogenesis, risk factors, classification, screening and treatment. Literature was searched using the following terms: “diabetic retinopathy pathogenesis and treatment”, “diabetic retinopathy screening”, “diabetic retinopathy risk factors”, “vascular endothelial growth factor inhibitors”, “laser photocoagulation” and “vitrectomy”. Brief description of the state of knowledge: DR is typically classified into two stages: non-proliferative DR, where the retinal vessels leak fluid or bleed and proliferative DR, characterized by the growth of abnormal blood vessels that can lead to retinal detachment or hemorrhaging. Treatment for DR aims to slow disease progression and preserve vision. Modern therapies include laser therapy, anti-VEGF injections and vitrectomy. Conclusions: Prevention is the most effective way to avoid vision loss from DR. Maintaining a healthy lifestyle, controlling blood glucose and blood pressure, as well as regular eye examinations are essential for managing DR. Therapeutic interventions such as anti-VEGF intravitreal injections, laser photocoagulation and vitrectomy proved to be very effective in DR management. Early intervention with modern therapies, patients education and treatment adherence are main factors in preventing severe outcomes of DR.